Preliminary outcomes of the introduction of computer assistance in total knee arthroplasty at the Basse-Terre hospital center in Guadeloupe - Adébola, Padonou; François, Amossou; Pascal, Chigblo; Eric, Lawson; Aristote, Hans-Moevi (International Surgery Journal, 2022)
Background: Computer-assisted total knee arthroplasty (TKA) is associated with significant precision during the surgical installation of prosthesis. We aimed to compare the radiological outcomes between the prostheses’ positioning assisted by a passive computer system and with the conventional technique. Methods: Participants included in this study were divided into two mixed groups based on the use of classical procedure and the computer navigated method during the positioning of implants during fractures. Clinical factors such as degrees of knee amplitude, knee IKS score and IKS function score and radiological features including the stage of osteoarthritis according to Ahlbäck classification, HKA and HKS angles, femoral and tibial mechanical axes, tibial slope prior and after the surgical procedure were measured in each group and then were compared. Results: Of a total of 92 patients, there were 63 women and 29 men; among which 42 patients for were treated with conventional TKA and 50 patients benefited from navigated TKA. 76 patients had stage IV osteoarthritis, 15 patients were at stage III of Albäck classification, and one patient at stage V. The postoperative HKA angle was found to be better in the navigated cohort with a statistically significant difference. The IKS knee and function scores are significantly better in the navigated cohort. Conclusions: Computer surgical navigation practiced during the total arthroplasty of the knee highlighted significant improvement in the positioning of the implants; and is associated with better functioning of the knees.